PENGARUH PENYULUHAN MENGGUNAKAN MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA ANAK TUNAGRAHITA - Nurjanah, Neneng; Permata, Diah Ayu; Praptiwi, Yenni Hendriani; Ningrum, Nining (Media Penelitian dan Pengembangan Kesehatan, 2023)
Children with intellectual disabilities have the right to receive health education to gain knowledge and effect positive changes toward a healthier lifestyle. The research intends to assess the impact of animated video-based counseling on the awareness of dental and oral hygiene among children with intellectual disabilities attending the Special Elementary School (SDLB) Negeri Bekasi Jaya in South Bekasi City. The study conducted in January and February 2023 utilized a pre-experimental design that followed a one-group pre-test and post-test approach. The research was conducted between January and February 2023, using a pre-experimental design with a one-group pre-test and post-test methodology. Technical terms are clarified upon their first mention, and any biased or emotional language has been omitted to maintain impartial clarity. The research concentrated on pupils with intellectual disabilities at SDLB Negeri Bekasi Jaya, situated in South Bekasi City. A purposive random sampling method was used to select a sample of 38 individuals who met the inclusion criteria of being cooperative children with IQ scores ranging from 60-to 85. The sample received a single treatment without any control. The study's results indicate that the mean pre-test score was 2.55, whereas the mean post-test score was 11.32. Analytical testing, using the Wilcoxon test, demonstrates a statistically significant result (P < 0.05), indicating a significant impact of counseling sessions through animated video media on children with intellectual disabilities' levels of knowledge. As a result, the study's findings strongly support animated graphics as an effective teaching tool for children with intellectual disabilities.